THE USE OF PICTURE DICTIONARY IN TEACHING THE MEANINGS OF VERBS TO THE SECOND YEARS STUDENT AT SMP PGRI 7 PALEMBANG - Nelya Juita (HOLISTICS, 2015)
The problem of this research is formulated as follows: “is it significantly effective to use a picture dictionary in teaching the meanings of verbs to the second year students?” therefore, the objectives of this investigation is to find out if it is significantly effective to use the picture dictionary in teaching the meanings of verbs to the students. The populations of this research was the second year students of SMP PGRI 7 Palembang in the academic year of 2004?2005. the number of the population was 22 students and the sample was all 22 students. The investigation was done through the quasi-experimental method, that is to describe the fact based on the data, which the writer got from the test. The test was given in two forms, matching and completion questions. The only technique used in collecting the data was a written test in the form of the pre-test and the post-test. The data were analyzed through  the formula of the  matched t-test. The result of this study indicated that after being taught the meanings of verbs, with their semantic picture using the given picture dictionary. Their average scores improved from the “poor” level (5) to the “ fair” level (6.75). it was supported by the result of the data analysis showed that the “t” obtained (1.902) exeeceded (1.895) as its critical value. It means the Ho was rejected and the Ha was accpeted. In other words, it was effective to usse the picture dictionary in teaching the meanings of verbs to the second year students at SMP PGRI 7 Palembang in the academic year of 2004/2005.